A new sporting horizon: a content analysis of Super Netball newspaper coverage. (May 2019) - English, Peter; Calder, Angela; Pearce, Simone; Kirby, Katy
A new professional netball competition in 2017 was part of a long-awaited boost for women's sport in Australia. Netball has a significant footprint across the country, being the nation's largest female participation team sport, and the national team is the reigning world champion. However, the sport has traditionally been underrepresented in both sports media and academic research. The new league was scheduled on free-to-air television after a landmark broadcast deal and the rise in media coverage reflected the growing commercial and public interest in female sport. As an example of this changing environment, it is important to examine what the coverage of women's netball involves. This descriptive study utilises a content analysis to explore the newspaper sports reporting of the first season of the Super Netball League. Specifically, it measures the amount and tone of coverage, the types of stories and descriptions employed in articles, including mentions of men's sport. Data have been collected from 703 articles from 15, 335 stories in newspaper sports sections of nine national, metropolitan and regional publications. While newspaper coverage of netball was comparable with other sports in terms of professionalism and content, there was still only a small amount of stories.